First report of Microtriatoma borbai Lent & Wygodzinsky, 1979 (Hemiptera, Reduviidae, Triatominae) in the state of Espirito Santo, Brazil: would M. borbai be living in eucalyptus crops? - Gil-Santana, Helcio Reinaldo; Martins, David dos Santos; Silva, Joao Bosco da; Oliveira, Jader de [UNESP] (Soc Brasileira Medicina Tropical, 2021)
Introduction: The occurrence of Microtriatoma borbai in the state of Espirito Santo, Brazil is reported by the first time. Methods: A triatomine specimen collected in a hybrid eucalyptus crop in the municipality of Aracruz, Espirito Santo state was found to be a male M. borbai. Results: This finding expands the geographical distribution of M. borbai from four to five Brazilian states. It is the first report of M. borbai occurrence inside a eucalyptus crop. Conclusions: The occurrence of M. borbai in the state of Espirito Santo broadens the geographical distribution of this species in southeastern Brazil.
Keywords: Biogeography; Bolboderini; Kissing bugs